1993
DOI: 10.1007/bf00042292
|View full text |Cite
|
Sign up to set email alerts
|

Miconazole: An effective antifungal agent for plant tissue culture

Abstract: Miconazole at concentrations between 5 and 20 mg 1-1 inhibited hyphal growth and sporulation in a wide range of fungi commonly associated with plants. These fungi included 4 Oomycetes, 11 Deuteromycetes, 4 Ascomycetes and 4 common airborne contaminants of plant tissue culture. The phytotoxicity of 20 mg 1-1 miconazole was also tested against a wide range of in vitro plant cultures.Shoot cultures from 15 species showed either no response or a slight growth reduction in the presence of miconazole. Although the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…When developing the MSTT formulation, we identified terbinafine as a candidate antifungal reagent from an earlier study that investigated squalene metabolism in Arabidopsis (Laranjeira et al ). We also tested miconazole (20 mg l −1 ) on the basis that it had been used to prevent fungal overgrowth in explant tissue culture of a number of crop species (Tynan et al ), but miconazole was 100% lethal to all of our Arabidopsis lines at this concentration (data not shown). It is possible that miconazole would be useful at lower concentrations but we did not pursue this further given our immediate success with terbinafine.…”
Section: Discussionmentioning
confidence: 99%
“…When developing the MSTT formulation, we identified terbinafine as a candidate antifungal reagent from an earlier study that investigated squalene metabolism in Arabidopsis (Laranjeira et al ). We also tested miconazole (20 mg l −1 ) on the basis that it had been used to prevent fungal overgrowth in explant tissue culture of a number of crop species (Tynan et al ), but miconazole was 100% lethal to all of our Arabidopsis lines at this concentration (data not shown). It is possible that miconazole would be useful at lower concentrations but we did not pursue this further given our immediate success with terbinafine.…”
Section: Discussionmentioning
confidence: 99%
“…Tynan et al found no significant phytotoxicity of miconazole (5-20 mg/L) on shoot cultures of nine plant species. Callus and hairy root cultures from five species were found to be more sensitive to miconazole than shoot cultures, although all these cultures showed a positive growth rate [7].…”
mentioning
confidence: 96%